Analisis Puisi Siapakah Engkau, Corona Karya Marhalim Zaini dengan Menggunakan Pendekatan Mimetik - Romadon, Mochammad Muchlis (CT. Rajawali media Utama, 2024)
As the Covid-19 situation gradually becomes more manageable with the implementation of new adaptations and the availability of vaccines provided by the government, society has begun to adapt. Throughout the pandemic, although social activities have been restricted, it has not limited the creation of literary works, including poetry that emerged amidst the Covid-19 pandemic. One such poem titled